The revised Common Time program as a strategy for student engagement and retention at university - Courtney Wright; Caroline Lenette; Stephen Lewis-Driver; Stephen Lamar (Student Success, 2017)
The School of Human Services and Social Work at Griffith University (Brisbane, Australia) developed the Common Time program in 2002 for its first year undergraduate students to increase student success in academic learning and to facilitate student engagement with staff and fellow students. Common Time consists of a series of facilitated forums during the initial weeks of each semester, where the first year cohort meet weekly to discuss general first year issues and receive information relevant to the first year university experience. As the program underwent changes in 2013, this paper discusses the findings of an evaluative research initiative. The results indicate that the revised 2013 Common Time program was, for the most part, effective in orientating and engaging these first year students during their transition into university study. However, further revisions to the program are needed to improve students opportunities to build meaningful social networks in particular.